2014
DOI: 10.1088/0953-2048/27/6/065017
|View full text |Cite
|
Sign up to set email alerts
|

Vortex pinning vs superconducting wire network: origin of periodic oscillations induced by applied magnetic fields in superconducting films with arrays of nanomagnets

Abstract: Abstract. Hybrid magnetic arrays embedded in superconducting films are ideal systems to study the competition between different physical (such as the coherence length) and structural length scales such as available in artificially produced structures. This interplay leads to oscillation in many magnetically dependent superconducting properties such as the critical currents, resistivity and magnetization. These effects are generally analyzed using two distinct models based on vortex pinning or wire network. In … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…7. The measurement of the critical current as a function of the magnetic field has been carried out for the sample with pitch 100 nm at 1.9 K in order to verify that a minimum in the resistance corresponds to a maximum in the critical current, as previously observed in other superconductors governed by pinning effects [3839 41,51]. In these measurements, the voltage is limited to a threshold value that corresponds to the crossover from the superconducting to the normal state of the sample.…”
Section: Resultsmentioning
confidence: 95%
“…7. The measurement of the critical current as a function of the magnetic field has been carried out for the sample with pitch 100 nm at 1.9 K in order to verify that a minimum in the resistance corresponds to a maximum in the critical current, as previously observed in other superconductors governed by pinning effects [3839 41,51]. In these measurements, the voltage is limited to a threshold value that corresponds to the crossover from the superconducting to the normal state of the sample.…”
Section: Resultsmentioning
confidence: 95%
“…The magnetoresistance curves are shifted right or left depending on the direction of the applied fields and the out-of-plane remanent magnetization in the dots. This means that superconducting vortices and antivortices are present in this situation and they coexist with the L-P effect in the wire network regime (16)(17)(18)(19). To figure out the exact origin of this magnetic influenced L-P effect we have to consider not only the vortex dynamics, but also the magnetism of the SCP dots and the direction of the applied fields, as it was discussed in the previous section.…”
Section: Resultsmentioning
confidence: 96%
“…To figure out the exact origin of this magnetic influenced L-P effect we have to consider not only the vortex dynamics, but also the magnetism of the SCP dots and the direction of the applied fields, as it was discussed in the previous section. Gomez et al (19) showed that effects related to vortex dynamics are present in the whole range of temperatures and they coexist with the L-P effect close to Tc0. The clear difference between the SN and SCP samples, although having the same geometry, indicates that the clue to understand the L-P effect in the SCP sample is the role played by the magnetic stray fields emerging from the outof-plane dot magnetization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations